Atherosclerosis, epigenetic modifications, and arterial stiffness - Piko, Nejc; Ekart, Robert; Bevc, Sebastjan; Hojs Radovan (Acta Medico-Biotechnica, 2021)
Atherosclerosis is a chronic, inflammatory vascular disease, characterized by progressive plaque build-up in the vessel wall, leading to tissue ischemia. It is the most common cause of cardiovascular diseases and is a major epidemiologic concern in modern society. The pathophysiology of atherosclerosis includes two main events: endothelial injury and vessel wall inflammation. Recent findings indicate that the pathogenesis of atherosclerosis involves dynamic changes in epigenetic modifications and gene expression in a cell type- and stage-specific manner. Epigenetics is the study of gene expression and involves phenotypical variations without genotypic changes. Three major epigenetic mechanisms participate in atherosclerosis: DNA methylation, posttranslational modifications of histones, and non-coding RNA molecules (long non-coding RNA molecules [lncRNAs] and microRNA molecules [miRNAs]). The field of epigenetics has opened up new diagnostic and therapeutic options. Arterial stiffness is increasingly recognized as a surrogate endpoint for cardiovascular disease. Pulse wave analysis (PWA) and pulse wave velocity (PWV), determined by applanation tonometry, provide essential information on central aortic stiffness. PWA and PWV are strongly correlated with atherosclerosis and can be used as a tool for assessing cardiovascular status and the risk of mortality and morbidity in patients with coronary disease, cerebrovascular disease, diabetes, arterial hypertension, and kidney disease.